Aprender a ensinar: como se produz o currículo situado de aprendizagem dos professores de cursos superiores de administração - Albuquerque, Letícia Zveiter de (2017)
Due to the growth in the number of degrees in Administration, the processes of evaluation of the HEI by the Federal Government and the pressures suffered by the teachers of these courses for a better quality of the teaching practiced that reflects in better results on the part of the students in the process of evaluation of the graduates, The objective of this work was to describe how to produce the situated learning curriculum of teacher of higher education courses. An analysis tool of the organizational learning process through its social learning bias, that is, through coexistence with its peers in organizations, the situated curriculum can be explained as the standard of opportunities available to beginners in their meetings with a specific community within the Organizations. The work was developed from a quantitative, descriptive and non-experimental research approach, using a survey-type questionnaire with 125 hourly and part-time teachers who currently teach in the undergraduate degree in Administration of Private Higher Education Institutions in the city of Rio de Janeiro and Greater Rio. From a bibliographical survey, the competences expected by the researchers to be developed by the professors of Higher Education of Administration were raised in 6 categories: for teaching, for management, for evaluation, Intrapersonal, Interpersonal and Technological. Each category was subdivided into knowledge, skills and attitudes for the higher education teacher in general and specifically for the teachers in Administration. The researcher listed and presented in the questionnaire: 19 types of knowledge; 37 types of skills and 18 types of attitudes. After analyzing the data, the situated curriculum of the teacher of Administration was constructed with: 6 types of knowledge, 24 types of abilities and the 18 types of attitudes that were configured as effectively having been acquired through social learning in HEIs were maintained.